SISTEM INFORMASI E-COMMERCE BERBASIS ANDROID PADA UMKM WARASIKO - Wara, Stefanus Sare (JURSIMA, 2022)
Researchers conducted research on Warasiko UMKM with the title Android-Based E-commerce Information System on Warasiko UMKM. This research aims to help the sales process at Warasiko UMKM, because the sales system is still the cause of the lack of income and settlement for Warasiko UMKM. The research method used is observation or observation, apart from observing the researcher also conducted interviews with UMKM owners and collected data in the form of interviews and documentation, in addition to the research method, in this study the design method that the researcher used was the waterfall method by following the stages contained therein. While the software testing method uses the Black Box Testing method. After conducting research, a problem was found, namely the sales system was still done manually, namely customers had to come directly to Warasiko UMKM to make transactions or purchase products.